2019
DOI: 10.1016/j.addbeh.2019.106047
|View full text |Cite
|
Sign up to set email alerts
|

JUUL in school: JUUL electronic cigarette use patterns, reasons for use, and social normative perceptions among college student ever users

Abstract: Background: JUUL electronic cigarettes have surged in popularity since their emergence on the market in 2015. JUUL is slim and simple in design and is capable of delivering cigarette-like levels of nicotine. However, little research has examined JUUL use patterns, reasons for use, and normative perceptions of JUUL among young adults. Methods: Participants were college students (N = 243) who reported ever using a JUUL electronic cigarette. Eligible participants completed a survey assessing JUUL use patterns, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 14 publications
(16 reference statements)
1
14
0
2
Order By: Relevance
“…While the students in our study described several reasons for vaping, peers and social influence seemed to play the largest role. This is also consistent with previous studies, which have described the importance of friends and peers on electronic cigarette use (Harrell et al, 2019; Leavens et al, 2019; Wallace & Roche, 2018). Prior studies on cigarette smoking have suggested that while youth may not feel directly pressured to smoke, an “unspoken pressure” exists when they are around peers who do (Clark et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the students in our study described several reasons for vaping, peers and social influence seemed to play the largest role. This is also consistent with previous studies, which have described the importance of friends and peers on electronic cigarette use (Harrell et al, 2019; Leavens et al, 2019; Wallace & Roche, 2018). Prior studies on cigarette smoking have suggested that while youth may not feel directly pressured to smoke, an “unspoken pressure” exists when they are around peers who do (Clark et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…College students “have historically been at the forefront of societal changes in substance use that later materialize within the general population” (Sutfin et al, 2013, p. 3). In a previous study, the most common reason for JUUL use among college students was because their friends had used, and nearly half of students reported their closest friends would approve of their use (Leavens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pod mod devices with USB charging capability and alluring flavors is a contributing factor to initiate vaping, especially among the youth 8,9 . JUUL pods are comprised of a heat resistant plastic enclosing the atomizer with a stainless steel vapor path, silica wick, and nichrome coil heater ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It was also limited in its assessment of the effect of GHWL, for example, it did not address the effects of GHWLs on bystanders who will be exposed to such GHWL but not through personal use. Such a prospect is likely to enhance the total population effect of applying GHWLs on ENDS devices, particularly given that peer influence is important for ENDS use (Leavens et al, 2019) and that conversations sparked by GHWLs are one of how they impact quit attempts (Morgan et al, 2018). Moreover, participants followed a fixed order of sessions to avoid any carryover effect (from GHWL to no GHWL), rather than randomized to the study conditions.…”
Section: Discussionmentioning
confidence: 99%